Battery composite isolating membrane and preparation method thereof
By using the first solid electrolyte particles with siloxane groups on the surface and the second solid electrolyte particles with surface coated modified in the lithium-ion battery separator, the problems of high impedance and low ionic conductivity of the existing separator are solved, and the electrochemical performance and safety of the lithium-ion battery are significantly improved.
Patent Information
- Application Number
- CN202411776896.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-28
AI Technical Summary
The high impedance and low ionic conductivity of existing lithium-ion batteries limit the electrochemical performance of lithium-ion batteries, especially the rate performance and high temperature safety performance.
A composite isolation film is used, which includes a polyolefin substrate, a first solid electrolyte particle having a silicone group on the surface and a second solid electrolyte particle having a PVDF, PEO, and PMMA coated modified. The first solid electrolyte particles are distributed in the inner holes of the polyolefin substrate, while the second solid electrolyte particles are distributed in the surface of the polyolefin substrate.
Effectively reduce the impedance of the diaphragm, improve ionic conductivity and safety, thereby improving the rate performance, cycle performance, safety performance and battery life of lithium-ion batteries.
Smart Images

Figure BDA0005171704790000171
Abstract
Description
Technical Field
[0001] The present invention relates to a battery composite isolation membrane, in particular to a composite isolation membrane with low impedance, high ion conductivity and high safety, and also to a preparation method of the composite isolation membrane. The composite isolation membrane is suitable for lithium-ion batteries, for example. Background Art
[0002] Battery separator is one of the important components of lithium-ion batteries. It has the functions of isolating positive and negative electrodes, preventing short circuits, and providing Li + The performance of the battery separator determines the internal resistance and interface structure of the lithium-ion battery, and affects the rate, cycle, capacity, and safety performance of the lithium-ion battery. Therefore, the battery separator has a key and important influence on the comprehensive performance of the lithium-ion battery.
[0003] Most of the battery separators currently available on the market are made of polyolefin materials. Such polyolefin separators have excellent electronic insulation, excellent mechanical strength, and good electrochemical stability. However, they have poor electrolyte wettability and low thermal stability, which makes the separator have high impedance and low ionic conductivity, greatly limiting the electrochemical performance of lithium-ion batteries, especially the rate performance and high-temperature safety performance.
[0004] At present, the main methods to solve the above problems are: (i) in the process of preparing the diaphragm, polyolefin is blended and extruded with inorganic or organic materials with good affinity for the electrolyte to prepare a composite diaphragm; (ii) polyolefin diaphragm is used as the substrate for organic and inorganic coating modification to prepare a coated composite diaphragm.
[0005] Chinese invention patent application publication number CN103199210A prepares a composite diaphragm with a porosity of 50% to 80% and good electrolyte retention rate by blending polyolefins with inorganic particles through extrusion, stretching, extraction, transverse or biaxial stretching, and heat treatment. Chinese invention patent application publication number CN112751138A prepares a composite isolation membrane with excellent mechanical properties and good liquid retention by blending polyolefins with fluororesin particles through extrusion, stretching, extraction, biaxial stretching, and heat treatment. The composite isolation membrane has the characteristics of excellent mechanical properties and good liquid retention, which can improve the safety and cycle life of lithium-ion batteries. Although the above patents improve the electrolyte wettability of the diaphragm to a certain extent, the inorganic particles and fluororesin particles used are inert materials and do not have ion conductivity. They cannot significantly reduce the impedance of the diaphragm or improve the ionic conductivity of the diaphragm.
[0006] Organic and inorganic coated modified polyolefin diaphragms include ceramic coated diaphragms, organic polymer coated diaphragms and solid electrolyte coated diaphragms. Such coated modified polyolefin diaphragms can improve the heat resistance of polyolefin diaphragms, and the electrolyte affinity is also very good, which can improve Li +The migration efficiency of lithium ions is improved, but the coating layer increases the migration path of lithium ions, resulting in an increase in the overall impedance of the coated modified polyolefin separator.
[0007] In general, the existing diaphragm technology has limited improvement in low impedance and high ionic conductivity performance, and cannot fully meet the current requirements for high rate, high safety, and high energy density of lithium-ion batteries. Summary of the invention
[0008] The purpose of the present invention is to provide a battery composite separator, which can effectively reduce impedance, improve ion conductivity and safety, thereby improving the rate performance, cycle performance, safety performance and endurance of lithium-ion batteries. In addition, the preparation process of the proposed battery composite separator is simplified, thereby reducing the preparation cost, and has high practicality and industrial production value.
[0009] The present invention provides a battery composite isolation membrane, comprising: a polyolefin substrate; a first solid electrolyte particle, the surface of which has a siloxane group; and a second solid electrolyte particle, the surface of which is coated and modified by one or more of PVDF, PEO, and PMMA; wherein the first solid electrolyte particles are distributed in the internal pores of the polyolefin substrate, and the second solid electrolyte particles are distributed on the surface of the polyolefin substrate.
[0010] Preferably, the mass fraction of the polyolefin substrate is 20 to 30, the mass fraction of the first solid electrolyte particles is 5 to 15, and the mass fraction of the second solid electrolyte particles is 5 to 15.
[0011] Preferably, the particle size of the second solid electrolyte particles is larger than that of the first solid electrolyte particles.
[0012] Preferably, the particle size of the first solid electrolyte particles is 10 nm to 50 nm, and the particle size of the second solid electrolyte particles is 50 nm to 100 nm.
[0013] Preferably, the first solid electrolyte particles are one or more of garnet-type solid electrolytes, sulfide solid electrolytes, and NASICON-type solid electrolytes, and the second solid electrolyte particles are one or more of garnet-type solid electrolytes, sulfide solid electrolytes, and NASICON-type solid electrolytes.
[0014] Preferably, the first solid electrolyte particles are lithium aluminum titanium phosphate (LATP), and the second solid electrolyte particles are lithium aluminum titanium phosphate (LATP).
[0015] Preferably, the polyolefin substrate includes ultra-high molecular weight polyethylene, linear polyethylene, branched polyethylene, and a density of 0.941 g / cm 3Up to 0.960g / cm 3 High-density polyethylene, density 0.915g / cm 3 Up to 0.940g / cm 3 One or more of low-density polyethylene, cross-linked polyethylene, and polypropylene.
[0016] Preferably, the polyolefin substrate comprises ultra-high molecular weight polyethylene having a weight average molecular weight of 1 million or more.
[0017] Preferably, the battery composite separator has a thickness of 3 μm to 50 μm, and a porosity of 35% to 70%.
[0018] Within the scope of the present invention, a method for preparing a battery composite isolation membrane is also proposed, comprising: stirring and mixing first solid electrolyte particles and a porogen to form a mixture I, wherein the surface of the first solid electrolyte particles has a siloxane group; stirring and mixing second solid electrolyte particles and the mixture I to form a mixture II, wherein the surface of the second solid electrolyte particles is coated and modified with one or more of PVDF, PEO, and PMMA; stirring and mixing polyolefin and the mixture II to form a mixture III; extruding the polymer III to form a sheet; biaxially stretching the sheet; extracting the biaxially stretched sheet; transversely stretching the extracted sheet for a second time; and heat treating the transversely stretched sheet for the second time to form a battery composite isolation membrane.
[0019] Preferably, the mass parts of the polyolefin are 20 to 30, the mass parts of the first solid electrolyte particles are 5 to 15, the mass parts of the second solid electrolyte particles are 5 to 15, and the mass parts of the porogen are 60 to 70.
[0020] Preferably, the particle size of the second solid electrolyte particles is larger than that of the first solid electrolyte particles.
[0021] Preferably, the particle size of the first solid electrolyte particles is 10 nm to 50 nm, and the particle size of the second solid electrolyte particles is 50 nm to 100 nm.
[0022] Preferably, the first solid electrolyte particles are one or more of garnet-type solid electrolytes, sulfide solid electrolytes, and NASICON-type solid electrolytes, and the second solid electrolyte particles are one or more of garnet-type solid electrolytes, sulfide solid electrolytes, and NASICON-type solid electrolytes.
[0023] Preferably, the first solid electrolyte particles are lithium aluminum titanium phosphate (LATP), and the second solid electrolyte particles are lithium aluminum titanium phosphate (LATP).
[0024] Preferably, the polyolefin includes ultra-high molecular weight polyethylene with a weight average molecular weight of 500,000 or more, linear polyethylene, branched polyethylene, and a density of 0.941 g / cm 3 Up to 0.960g / cm 3 High-density polyethylene, density 0.915g / cm 3 Up to 0.940g / cm 3 One or more of low-density polyethylene, cross-linked polyethylene, and polypropylene.
[0025] Preferably, the polyolefin comprises ultra-high molecular weight polyethylene having a weight average molecular weight of 1 million or more.
[0026] Preferably, the step of extruding to form a sheet comprises: adding the mixture III into a twin-screw extruder for hot shear extrusion; passing the hot shear extruded mixture III through a die to form a cast body; and cooling the cast body to form the sheet.
[0027] In the present invention, the first solid electrolyte particles having siloxane groups on the surface are distributed in the internal pores of the polyolefin substrate, thereby reducing the membrane impedance while maintaining the mechanical strength of the membrane, thereby improving the Li + The second solid electrolyte particles with a surface modified by one or more of PVDF, PEO, and PMMA are distributed on the surface of the polyolefin substrate, which can participate in the formation of SEI and solidify the electrolyte to form a solid electrolyte film, reducing the amount of liquid electrolyte used in the battery, making it difficult for the battery to form lithium dendrites, greatly improving the battery safety and cycle life. In addition, the surface modification group of the second solid electrolyte particles has good absorption and retention performance for the electrolyte, which can improve the Li + Migration rate and conductivity. DETAILED DESCRIPTION
[0028] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0029] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article.
[0030] The first embodiment of the present invention is achieved as follows:
[0031] A battery composite separator, comprising: a polyolefin substrate; a first solid electrolyte particle; and a second solid electrolyte particle. In addition, the surface of the first solid electrolyte particle has a siloxane group and is distributed in the internal pores of the polyolefin substrate, and the surface of the second solid electrolyte particle is coated and modified by one or more of PVDF, PEO, and PMMA and is distributed on the surface of the polyolefin substrate. The thickness of the battery composite separator can be 3μm to 50μm, preferably 4μm to 30μm, more preferably 7μm to 10μm, and particularly preferably 9μm. The porosity of the battery composite separator can be 35% to 70%, preferably 35% to 60%, and more preferably 47%.
[0032] The mass parts of the polyolefin substrate may be 20 to 30, the mass parts of the first solid electrolyte particles may be 5 to 15, and the mass parts of the second solid electrolyte particles may be 5 to 15; preferably, the mass parts of the polyolefin substrate are 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, or 30, the mass parts of the first solid electrolyte particles are 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15, and the mass parts of the second solid electrolyte particles are 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15; more preferably, the mass parts of the polyolefin substrate are 20 or 30, the mass parts of the first solid electrolyte particles are 5, 10, or 15, and the mass parts of the second solid electrolyte particles are 5, 10, or 15.
[0033] Based on the total mass of the battery composite separator, the polyolefin substrate may account for 40wt% to 75wt%, the first solid electrolyte particles may account for 10wt% to 37.5wt%, and the second solid electrolyte particles may account for 10wt% to 37.5wt%; preferably, the polyolefin substrate accounts for 40wt%, 42wt%, 44wt%, 46wt%, 48wt%, 50wt%, 52wt%, 54wt%, 56wt%, 58wt%, 60wt%, 62wt%, 64wt%, 66wt%, 68wt%, 70wt%, 72wt%, 74wt%, or 75wt%, and the first solid electrolyte particles account for 10wt%, 12wt%, 14wt%, 16wt%, 18wt%. %, 20wt%, 22wt%, 24wt%, 26wt%, 28wt%, 30wt%, 32wt%, 34wt%, 36wt%, or 37.5wt%; the second solid electrolyte particles account for 10wt%, 12wt%, 14wt%, 16wt%, 18wt%, 20wt%, 22wt%, 24wt%, 26wt%, 28wt%, 30wt%, 32wt%, 34wt%, 36wt%, or 37.5wt%; more preferably, the polyolefin substrate accounts for 40wt% or 60wt%, the first solid electrolyte particles account for 10wt%, 20wt%, or 30wt%, and the second solid electrolyte particles account for 10wt%, 20wt%, or 30wt%.
[0034] The polyolefin substrate may include ultra-high molecular weight polyethylene with a weight average molecular weight of 500,000 or more, linear polyethylene, branched polyethylene, a density of 0.941 g / cm 3 Up to 0.960g / cm 3 High-density polyethylene, density 0.915g / cm 3 Up to 0.940g / cm 3 Preferably, the polyolefin substrate comprises one or more of low-density polyethylene, cross-linked polyethylene, and polypropylene; preferably, the polyolefin substrate comprises ultra-high molecular weight polyethylene with a weight average molecular weight of 1 million or more; more preferably, the polyolefin substrate comprises ultra-high molecular weight polyethylene with a weight average molecular weight of 1 million.
[0035] The first solid electrolyte particles may be one or more of a garnet-type solid electrolyte, a sulfide solid electrolyte, and a NASICON-type solid electrolyte. The garnet-type solid electrolyte may have a chemical formula of Li x Ln3M2O 12Indicates that Ln is La or Y, M is one or more of Zr, Nb, Sn, Sb, Te, Hf, Ta, and x is between 3 and 7; the sulfide solid electrolyte may be one or more of LGPS, LPS, LPSCl, LSnPS, LSiPS, LGSiPS, LAlPS, LGS, LGZS, LSiS, and LSA1S; the NASICON solid electrolyte may be one or more of lithium aluminum titanium phosphate (LATP), lithium aluminum germanium phosphate (LAGP), and lithium zirconium phosphate (LZP). In addition, the particle size D of the first solid electrolyte particles is 50 It can be 10 nm to 50 nm, preferably 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, or 50 nm.
[0036] The second solid electrolyte particles may be one or more of a garnet-type solid electrolyte, a sulfide solid electrolyte, and a NASICON-type solid electrolyte. The garnet-type solid electrolyte may have a chemical formula of Li x Ln3M2O 12 Indicates that Ln is La or Y, M is one or more of Zr, Nb, Sn, Sb, Te, Hf, Ta, and x is between 3 and 7; the sulfide solid electrolyte may be one or more of LGPS, LPS, LPSCl, LSnPS, LSiPS, LGSiPS, LA1PS, LGS, LGZS, LSiS, and LSAlS; the NASICON-type solid electrolyte may be one or more of lithium aluminum titanium phosphate (LATP), lithium aluminum germanium phosphate (LAGP), and lithium zirconium phosphate (LZP). In addition, the particle size of the second solid electrolyte particles may be 50nm to 100nm, preferably 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, or 100nm. Moreover, the particle size of the second solid electrolyte particles may be greater than or equal to the particle size of the first solid electrolyte particles; preferably, the particle size of the second solid electrolyte particles is greater than the particle size of the first solid electrolyte particles.
[0037] The second embodiment of the present invention is achieved as follows:
[0038] A method for preparing a battery composite separator comprises: stirring and mixing first solid electrolyte particles and a porogen to form a mixture I, wherein the surface of the first solid electrolyte particles has a siloxane group; stirring and mixing second solid electrolyte particles and the mixture I to form a mixture II, wherein the surface of the second solid electrolyte particles is coated and modified by one or more of PVDF, PEO, and PMMA; stirring and mixing polyolefin and the mixture II to form a mixture III; extruding the polymer III to form a sheet; biaxially stretching the sheet; extracting the biaxially stretched sheet; transversely stretching the extracted sheet for a second time; and heat treating the transversely stretched sheet for a second time to form a battery composite separator. The battery composite separator may have a thickness of 3 μm to 50 μm, preferably 4 μm to 30 μm, more preferably 7 μm to 10 μm, and particularly preferably 9 μm. The battery composite separator may have a porosity of 35% to 70%, preferably 35% to 60%, and more preferably 47%.
[0039] The first solid electrolyte particles may be one or more of a garnet-type solid electrolyte, a sulfide solid electrolyte, and a NASICON-type solid electrolyte. The garnet-type solid electrolyte may have a chemical formula of Li x Ln3M2O 12 Indicates that Ln is La or Y, M is one or more of Zr, Nb, Sn, Sb, Te, Hf, Ta, and x is between 3 and 7; the sulfide solid electrolyte may be one or more of LGPS, LPS, LPSCl, LSnPS, LSiPS, LGSiPS, LAlPS, LGS, LGZS, LSiS, and LSA1S; the NASICON solid electrolyte may be one or more of lithium aluminum titanium phosphate (LATP), lithium aluminum germanium phosphate (LAGP), and lithium zirconium phosphate (LZP). In addition, the particle size D of the first solid electrolyte particles is 50 It can be 10 nm to 50 nm, preferably 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, or 50 nm.
[0040] The porogen may be one or more of phthalate, sebacate, adipate, phosphate, and white oil, preferably white oil.
[0041] The second solid electrolyte particles may be one or more of a garnet-type solid electrolyte, a sulfide solid electrolyte, and a NASICON-type solid electrolyte. The garnet-type solid electrolyte may have a chemical formula of Li x Ln3M2O 12Indicates that Ln is La or Y, M is one or more of Zr, Nb, Sn, Sb, Te, Hf, Ta, and x is between 3 and 7; the sulfide solid electrolyte may be one or more of LGPS, LPS, LPSCl, LSnPS, LSiPS, LGSiPS, LA1PS, LGS, LGZS, LSiS, and LSAlS; the NASICON-type solid electrolyte may be one or more of lithium aluminum titanium phosphate (LATP), lithium aluminum germanium phosphate (LAGP), and lithium zirconium phosphate (LZP). In addition, the particle size of the second solid electrolyte particles may be 50nm to 100nm, preferably 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, or 100nm. Moreover, the particle size of the second solid electrolyte particles may be greater than or equal to the particle size of the first solid electrolyte particles; preferably, the particle size of the second solid electrolyte particles is greater than the particle size of the first solid electrolyte particles.
[0042] The polyolefin may include ultra-high molecular weight polyethylene with a weight average molecular weight of 500,000 or more, linear polyethylene, branched polyethylene, a density of 0.941 g / cm 3 Up to 0.960g / cm 3 High-density polyethylene, density 0.915g / cm 3 Up to 0.940g / cm 3 Preferably, the polyolefin comprises one or more of low-density polyethylene, cross-linked polyethylene, and polypropylene; preferably, the polyolefin comprises an ultra-high molecular weight polyethylene having a weight average molecular weight of 1 million or more; more preferably, the polyolefin comprises an ultra-high molecular weight polyethylene having a weight average molecular weight of 1 million.
[0043] The mass parts of the polyolefin may be 20 to 30, the mass parts of the first solid electrolyte particles may be 5 to 15, the mass parts of the second solid electrolyte particles may be 5 to 15, and the mass parts of the porogen may be 60 to 70; preferably, the mass parts of the polyolefin are 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, or 30, the mass parts of the first solid electrolyte particles are 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15, and the mass parts of the porogen are 60 to 70. The mass parts of the second solid electrolyte particles are 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15, and the mass parts of the porogen are 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, or 70; more preferably, the mass parts of the polyolefin are 20 or 30, the mass parts of the first solid electrolyte particles are 5, 10, or 15, the mass parts of the second solid electrolyte particles are 5, 10, or 15, and the mass parts of the porogen are 60 or 70.
[0044] The steps of forming mixture I, forming mixture II, and forming mixture III can be performed at room temperature. The so-called "room temperature" refers to a temperature range of about 25°C, preferably 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C, or 30°C.
[0045] In the step of forming the mixture III, based on the total mass of the mixture III, the polyolefin may account for 16.7wt% to 30wt%, the first solid electrolyte particles may account for 4.2wt% to 15wt%, the second solid electrolyte particles may account for 4.2wt% to 15wt%, and the porogen may account for 50wt% to 70wt%; preferably, the polyolefin accounts for 20wt% or 25wt%, the first solid electrolyte particles account for 4.2wt%, 8.3wt%, or 15wt%, the second solid electrolyte particles account for 5wt%, 8.3wt%, or 12.5wt%, and the porogen accounts for 58.3wt% or 60wt%.
[0046] In the step of extruding to form a sheet, the mixture III can be first added to a twin-screw extruder for hot shear extrusion, and then the hot shear extruded mixture III is passed through a die to form a cast body, and finally the cast body is cooled to form the sheet. In addition, in the step of hot shear extrusion, the extrusion temperature of the twin-screw extruder can be 150°C to 260°C, preferably 250°C; and the screw speed can be 80rpm to 300rpm. In the step of forming a cast body, the hot shear extruded mixture III can be passed through a hanger-type die. The so-called "hanger-type die" can refer to the Chinese invention patent application publication number CN112297380B or CN116666896B. In the cooling step, the cast body can be passed through a cooling roller, and the cooling temperature of the cooling roller can be 0°C to 50°C, preferably 20°C. Furthermore, in the cooling step, the sheet thickness may be 300 μm to 4000 μm, preferably 600 μm.
[0047] In the step of biaxially stretching the sheet, the stretching ratio between the longitudinal direction and the transverse direction can be 6 to 60 times, preferably 8 times; and the stretching temperature can be 105°C to 120°C, preferably 105°C.
[0048] In the step of extracting the sheet, the biaxially stretched sheet may be passed through an extractant and allowed to remain there for 1 to 20 minutes, and the extractant is preferably dichloromethane, and the residence time is preferably 10 minutes.
[0049] In the step of secondary transverse stretching of the sheet, the stretching ratio can be 1.1 to 1.3 times, preferably 1.2 times; the retraction ratio can be 1 to 1.1 times, preferably 1.05 times; and the stretching temperature can be 105°C to 125°C, preferably 120°C.
[0050] In the step of heat treating the sheet, the heat treatment time may be 0.5 to 3 minutes, preferably 0.5 minutes, and the heat treatment temperature may be 110 to 150° C., preferably 130° C. In addition, air heating or roller heating may be used to heat treat the secondarily transversely stretched sheet.
[0051] It should be noted that the first solid electrolyte particles with siloxane groups on the surface will be distributed at the interface between the polyolefin and the porogen, and act as defects to induce solid-liquid separation when the polyolefin and the porogen are separated in solid and liquid, so the holes of the polyolefin substrate will preferentially occur in the place where the first solid electrolyte particles with siloxane groups on the surface are present. In addition, the first solid electrolyte particles with siloxane groups on the surface have better affinity with the porogen and tend to be distributed at the interface between the porogen and the polyolefin; the second solid electrolyte particles with one or more coated and modified PVDF, PEO, and PMMA on the surface have better affinity with the polyolefin and tend to be distributed on the polyolefin; through this, the first solid electrolyte particles with siloxane groups on the surface are distributed in the internal holes of the polyolefin substrate, and the second solid electrolyte particles with one or more coated and modified PVDF, PEO, and PMMA on the surface are distributed on the surface of the polyolefin substrate. The preparation method proposed in this embodiment can be used to prepare the battery composite separator proposed in the first embodiment, but the preparation method proposed in this embodiment should not limit the battery composite separator proposed in the first embodiment.
[0052] The present invention is illustrated by the following examples:
[0053] Example 1
[0054] 5 parts by mass of siloxane-modified LATP particles with a particle size of 10 nm as the first solid electrolyte particles are stirred evenly with 70 parts by mass of white oil at room temperature to form a mixture I; 15 parts by mass of PVDF-modified LATP particles with a particle size of 70 nm as the second solid electrolyte particles are stirred evenly with the mixture I to form a mixture II; 30 parts by mass of polyethylene particles with a weight-average molecular weight of 1,000,000 are mixed and stirred evenly with the mixture II, and then added into a twin-screw extruder to obtain an oil film with a thickness of 600 μm, and the obtained oil film is stretched 8 times in the longitudinal direction and the transverse direction at a stretching temperature of 105°C, and the stretched film is placed in an extraction tank filled with dichloromethane and kept for 10 minutes; after extraction and drying, it enters a transverse stretching machine, is stretched 1.2 times in the transverse direction and then retracted 1.05 times, and the transverse stretching temperature is 120°C; finally, a heat treatment is performed, the hot air temperature is 130°C, and the treatment time is 0.5 minutes.
[0055] Example 2
[0056] 15 parts by mass of siloxane-modified LAGP particles with a particle size of 40 nm as the first solid electrolyte particles are stirred evenly with 60 parts by mass of white oil at room temperature to form a mixture I; 5 parts by mass of PMMA-modified LATP particles with a particle size of 50 nm as the second solid electrolyte particles are stirred evenly with the mixture I to form a mixture II; 20 parts by mass of polyethylene particles with a weight-average molecular weight of 1,000,000 are mixed and stirred evenly with the mixture II, and then added into a twin-screw extruder to obtain an oil film with a thickness of 600 μm, and the obtained oil film is stretched 8 times in the longitudinal and transverse directions at a stretching temperature of 105°C, and the stretched film is placed in an extraction tank filled with dichloromethane and kept for 10 minutes; after extraction and drying, it enters a transverse stretching machine, is stretched 1.2 times in the transverse direction and then retracted 1.05 times, and the transverse stretching temperature is 120°C; finally, a heat treatment is performed, the hot air temperature is 130°C, and the treatment time is 0.5 minutes.
[0057] Example 3
[0058] 10 parts by mass of siloxane-modified LATP particles with a particle size of 30 nm as the first solid electrolyte particles are stirred evenly with 70 parts by mass of white oil at room temperature to form a mixture I; 10 parts by mass of PVDF-modified LATP particles with a particle size of 60 nm as the second solid electrolyte particles are stirred evenly with the mixture I to form a mixture II; 30 parts by mass of polyethylene particles with a weight-average molecular weight of 1,000,000 are mixed and stirred evenly with the mixture II, and then added into a twin-screw extruder to obtain an oil film with a thickness of 600 μm, and the obtained oil film is stretched 8 times in the longitudinal direction and the transverse direction at a stretching temperature of 105° C. The stretched film is placed in an extraction tank filled with dichloromethane and kept for 10 minutes; after extraction and drying, it enters a transverse stretching machine, is stretched 1.2 times in the transverse direction and then retracted 1.05 times, and the transverse stretching temperature is 120° C.; finally, a heat treatment is performed, the hot air temperature is 130° C., and the treatment time is 0.5 minutes.
[0059] Comparative Example 1
[0060] 5 parts by mass of siloxane-modified LATP particles with a particle size of 10 nm as the first solid electrolyte particles are stirred evenly with 70 parts by mass of white oil at room temperature to form a mixture I; 15 parts by mass of siloxane-modified LATP particles with a particle size of 10 nm as the second solid electrolyte particles are stirred evenly with the mixture I to form a mixture II; 30 parts by mass of polyethylene particles with a weight-average molecular weight of 1,000,000 are mixed and stirred evenly with the mixture II, and then added into a twin-screw extruder to obtain an oil film with a thickness of 600 μm, and the obtained oil film is stretched 8 times in the longitudinal and transverse directions at a stretching temperature of 105°C, and the stretched film is placed in an extraction tank filled with dichloromethane and kept for 10 minutes; after extraction and drying, it enters a transverse stretching machine, is stretched 1.2 times in the transverse direction and then retracted 1.05 times, and the transverse stretching temperature is 120°C; finally, a heat treatment is performed, the hot air temperature is 130°C, and the treatment time is 0.5 minutes.
[0061] Comparative Example 2
[0062] 5 parts by mass of PVDF modified LATP particles with a particle size of 70 nm as the first solid electrolyte particles are stirred evenly with 70 parts by mass of white oil at room temperature to form a mixture I; 15 parts by mass of PVDF modified LATP particles with a particle size of 70 nm as the second solid electrolyte particles are stirred evenly with the mixture I to form a mixture II; 30 parts by mass of polyethylene particles with a weight average molecular weight of 1 million are mixed and stirred evenly with the mixture II, and then added into a twin-screw extruder to obtain an oil film with a thickness of 600 μm, and the obtained oil film is stretched 8 times in the longitudinal and transverse directions at a stretching temperature of 105°C, and the stretched film is placed in an extraction tank filled with dichloromethane and kept for 10 minutes; after extraction and drying, it enters a transverse stretching machine, is stretched 1.2 times in the transverse direction and then retracted 1.05 times, and the transverse stretching temperature is 120°C; finally, a heat treatment is performed, the hot air temperature is 130°C, and the treatment time is 0.5 minutes.
[0063] The specific test methods used in this article are described as follows:
[0064] 1. Thickness (GB / T 6672-2001)
[0065] The thickness of the film was measured using a Millimar C1208 film thickness gauge (Millimar, Germany).
[0066] 2. Porosity
[0067] Take a membrane with a mass between 0.6g and 1.0g, weigh the mass m, and measure the area s; first remove the bubbles on the surface of the base membrane in a water tank, and then put the base membrane into a water cup under water for later use. Place the prepared membrane on the water pressure instrument, input the sample mass m and area s and test, and finally obtain the porosity value after spectrum analysis.
[0068] 3. Internal resistance and ionic conductivity (GB / T 36363-2018)
[0069] Test the thickness L of the diaphragm to be tested; cut the diaphragm that matches the size of the resistance test mold, record the diaphragm area as S, put the cut diaphragm into the electrolyte of 1mol LiPF6, EC / EMC / DMC=1:1:1Vol%, keep it sealed, and soak for 2h. Inject the electrolyte into the resistance test mold and put the diaphragm in. Test its AC impedance resistance R*S, ionic conductivity σ=L / (R*S); test 5 times, and the average value is the internal resistance and ionic conductivity of the diaphragm.
[0070] 4. Contact angle
[0071] The composition and content of the lithium battery electrolyte are 1 mol LiPF6, EC / EMC / DMC=1:1:1 Vol%.
[0072] 5. Liquid absorption rate
[0073] Cut the membrane to be tested into samples of a certain size, weigh the mass of the sample m1, and soak the sample in 1 mol / L LiPF6 / (EC:EMC) electrolyte (EC:EMC volume ratio 1:1) for 24 hours. After taking out, gently wipe off the excess electrolyte on the surface of the sample with filter paper, and then weigh it and record it as m2. The liquid absorption rate of the membrane (%) = (m2-m1) / m1×100%.
[0074] From Table 1, it can be seen that the simultaneous use of two different solid electrolyte particles can reduce the internal resistance of the diaphragm, improve the ionic conductivity, and improve the liquid absorption rate compared to the use of a single solid electrolyte particle. Moreover, further comparison of Example 1 with Comparative Examples 1 and 2 shows that the expected characteristics of the diaphragm obtained by combining the diaphragm characteristics of using only siloxane-modified LATP particles as solid electrolyte particles and the diaphragm characteristics of using only PVDF-modified LATP particles as solid electrolyte particles are not as good as the diaphragm characteristics of using siloxane-modified LATP particles and PVDF-modified LATP particles as solid electrolyte particles, indicating that the simultaneous use of two different solid electrolyte particles has unpredictable improvements in diaphragm characteristics.
[0075] Table 1
[0076]
[0077]
[0078] The above contents involving common knowledge are not described in detail, and those skilled in the art can understand them.
[0079] The above descriptions are only some specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention shall be included in the protection scope of the present invention. The technical scope of the present invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.
Claims
1. A battery composite separator, characterized in that: include: A polyolefin substrate; a first solid electrolyte particle having a siloxane group on its surface; as well as A second solid electrolyte particle, the surface of which is coated and modified by one or more of PVDF, PEO, and PMMA; The first solid electrolyte particles are distributed in the inner pores of the polyolefin substrate, and the second solid electrolyte particles are distributed on the surface of the polyolefin substrate.
2. The battery composite separator according to claim 1, characterized in that: The mass parts of the polyolefin substrate are 20 to 30, the mass parts of the first solid electrolyte particles are 5 to 15, and the mass parts of the second solid electrolyte particles are 5 to 15.
3. The battery composite separator according to claim 2, characterized in that: The particle size of the second solid electrolyte particles is larger than that of the first solid electrolyte particles.
4. The battery composite separator according to claim 3, characterized in that: The particle size of the first solid electrolyte particles is 10 nm to 50 nm, and the particle size of the second solid electrolyte particles is 50 nm to 100 nm.
5. The battery composite separator according to claim 1, characterized in that: The first solid electrolyte particles are one or more of garnet-type solid electrolytes, sulfide solid electrolytes, and NASICON-type solid electrolytes, and the second solid electrolyte particles are one or more of garnet-type solid electrolytes, sulfide solid electrolytes, and NASICON-type solid electrolytes.
6. The battery composite separator according to claim 1, characterized in that: The first solid electrolyte particles are lithium aluminum titanium phosphate (LATP), and the second solid electrolyte particles are lithium aluminum titanium phosphate (LATP).
7. The battery composite separator according to claim 1, characterized in that: The polyolefin substrate includes ultra-high molecular weight polyethylene with a weight average molecular weight of 500,000 or more, linear polyethylene, branched polyethylene, and a density of 0.941 g / cm 3 Up to 0.960g / cm 3 High-density polyethylene, density 0.915g / cm 3 Up to 0.940g / cm 3 One or more of low-density polyethylene, cross-linked polyethylene, and polypropylene.
8. The battery composite separator according to claim 1, characterized in that: The polyolefin substrate includes ultra-high molecular weight polyethylene having a weight average molecular weight of 1 million or more.
9. The battery composite separator according to claim 1, characterized in that: The battery composite separator has a thickness of 3 μm to 50 μm, and a porosity of 35% to 70%.
10. A method for preparing a battery composite separator, characterized in that: include: Stirring and mixing first solid electrolyte particles and a porogen to form a mixture I, wherein the surfaces of the first solid electrolyte particles have siloxane groups; The second solid electrolyte particles are stirred and mixed evenly with the mixture I to form a mixture II, wherein the surfaces of the second solid electrolyte particles are coated and modified by one or more of PVDF, PEO, and PMMA; Stirring and mixing the polyolefin and the mixture II to form a mixture III; Extruding the polymer III into a sheet; Biaxially stretching the sheet; Extracting the biaxially stretched sheet; Secondarily transversely stretching the extracted sheet; as well as The secondary transversely stretched sheet is heat treated to form a battery composite separator.
11. The method for preparing a composite battery separator according to claim 10, characterized in that: The mass parts of the polyolefin are 20 to 30, the mass parts of the first solid electrolyte particles are 5 to 15, the mass parts of the second solid electrolyte particles are 5 to 15, and the mass parts of the porogen are 60 to 70.
12. The method for preparing a composite battery separator according to claim 11, characterized in that: The particle size of the second solid electrolyte particles is larger than that of the first solid electrolyte particles.
13. The method for preparing a composite battery separator according to claim 12, characterized in that: The particle size of the first solid electrolyte particles is 10 nm to 50 nm, and the particle size of the second solid electrolyte particles is 50 nm to 100 nm.
14. The method for preparing a composite battery separator according to claim 10, characterized in that: The first solid electrolyte particles are one or more of garnet-type solid electrolytes, sulfide solid electrolytes, and NASICON-type solid electrolytes, and the second solid electrolyte particles are one or more of garnet-type solid electrolytes, sulfide solid electrolytes, and NASICON-type solid electrolytes.
15. The method for preparing a composite battery separator according to claim 10, characterized in that: The first solid electrolyte particles are lithium aluminum titanium phosphate (LATP), and the second solid electrolyte particles are lithium aluminum titanium phosphate (LATP).
16. The method for preparing a composite battery separator according to claim 10, characterized in that: The polyolefins include ultra-high molecular weight polyethylene with a weight average molecular weight of 500,000 or more, linear polyethylene, branched polyethylene, and a density of 0.941 g / cm 3 Up to 0.960g / cm 3 High-density polyethylene, density 0.915g / cm 3 Up to 0.940g / cm 3 One or more of low-density polyethylene, cross-linked polyethylene, and polypropylene.
17. The method for preparing a composite battery separator according to claim 10, characterized in that: The polyolefin includes ultra-high molecular weight polyethylene having a weight average molecular weight of 1 million or more.
18. The method for preparing a composite battery separator according to claim 10, characterized in that: The step of extruding to form a sheet comprises: Adding the mixture III into a twin-screw extruder and extruding it through hot shearing; Passing the hot shear extruded mixture III through a die to form a cast body; and The cast body is cooled to form the sheet.
Citation Information
Patent Citations
Lithium ion battery diaphragm
CN103199210A
Lithium-ion battery separators, electrochemical devices, and methods for improving the lateral thickness distribution of thin-film castings and saving material in the die head.
CN112297380B
High-performance lithium ion battery composite isolating membrane
CN112751138A
Cited By
Semi-solid battery diaphragm and preparation method thereof
CN122552756A